1983
DOI: 10.1001/archderm.119.8.675
|View full text |Cite
|
Sign up to set email alerts
|

Serum triglyceride elevation following high-dose vitamin A treatment for pityriasis rubra pilaris

Abstract: We describe two patients with pityriasis rubra pilaris in whom hypertriglyceridemia developed following the oral administration of high-dose vitamin A (retinol). The effects of transient hypertriglyceridemia are unknown, as both patients tolerated high-dose vitamin A therapy with minor, if any, other side effects. Both patients had minimal clinical improvement with this therapy. Patients being treated with 1,000,000 IU of vitamin A each day for ten to 14 days should have frequent determinations of serum lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Interestingly, VA supplementation significantly increased the serum triglyceride concentration in the NFD cohort (NFD + VA compared with NFD). It was also reported in previous case studies that serum triglyceride concentration was elevated in patients receiving isotretinoin (13-cis-RA) for acne ( 54 ) or after a high-dose VA treatment to patients with pityriasis rubra pilaris ( 55 ). The mechanism is unknown.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, VA supplementation significantly increased the serum triglyceride concentration in the NFD cohort (NFD + VA compared with NFD). It was also reported in previous case studies that serum triglyceride concentration was elevated in patients receiving isotretinoin (13-cis-RA) for acne ( 54 ) or after a high-dose VA treatment to patients with pityriasis rubra pilaris ( 55 ). The mechanism is unknown.…”
Section: Discussionmentioning
confidence: 62%
“…However, the main predictor of vitamin A levels among the variables studied herein was triglyceride, which explained 18% of its variance, suggesting a link between this vitamin and triglyceride metabolism. In keeping with this, it has been reported that oral administration of retinol or other retinoids causes an increase in circulating triglyceride [50–52]. Retinoids enhance the transcription of the human apoC‐III gene – whose product antagonizes the catabolism of triglyceride‐rich lipoproteins [53]– via the retinoid X receptor (RXR) [54], which recognizes the vitamin A derivative 9‐ cis ‐retinoic acid as a natural ligand [28].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have consistently shown no significant effect of b-carotene supplementation on serum total cholesterol, HDL cholesterol or triglyceride levels [21][22][23][24][25][26]. However, retinoids such as isotretinoin (13-cis retinoic acid) and etretinate, as well as high doses of vitamin A are known to increase triglycerides and cholesterol levels and lower HDL levels [6][7][8][9][10][11], changes associated with an increased risk of coronary heart disease [14]. Whether chronic supplementation with retinol might have similar effects on lipids, especially HDL and LDL cholesterol, has not been well investigated, and was the focus of this study.…”
Section: Discussionmentioning
confidence: 99%